Migration Mobility: a critical approach to hydraulic metaphors - Dias, Gustavo (2019)
This article unfolds the concept of migration mobility. Through a critical review of migratory studies which investigate such social dynamic based on hydraulic metaphors such as flow or migration wave, I stress the importance of a dialogue with other study areas. Border and mobile studies are the two fields explored in more details here. In order to engage in a fruitful dialogue with migration studies, I particularly demonstrate how conceptual tools - smart borders, social space, and journey -bring significant contributions to thinking about migration as a tactical mobility intertwined with borders.